Is a reduction in distance to nearest supermarket associated with BMI change among type 2 diabetes patients?. (July 2016) - Zhang, Y. Tara; Laraia, Barbara A.; Mujahid, Mahasin S.; Blanchard, Samuel D.; Warton, E. Margaret; Moffet, Howard H.; Karter, Andrew J.
Abstract: We examined whether residing within 2 miles of a new supermarket opening was longitudinally associated with a change in body mass index (BMI). We identified 12 new supermarkets that opened between 2009 and 2010 in 8 neighborhoods. Using the Kaiser Permanente Northern California Diabetes Registry, we identified members with type 2 diabetes residing continuously in any of these neighborhoods 12 months prior to the first supermarket opening until 10 months following the opening of the last supermarket. Exposure was defined as a reduction (yes/no) in travel distance to the nearest supermarket as a result of a new supermarket opening. First difference regression models were used to estimate the impact of reduced supermarket distance on BMI, adjusting for longitudinal changes in patient and neighborhood characteristics. Among patients in the exposed group, new supermarket openings reduced travel distance to the nearest supermarket by 0.7 miles on average. However, reduced distance to nearest supermarket was not associated with BMI changes. Overall, we found no evidence that reduced supermarket distance was associated with reduced levels of obesity for residents with type 2 diabetes. Highlights: Longitudinal research on supermarket access and health are rare but needed. We assessed BMI for diabetes patients living near 12 new supermarket developments. For many, the new developments cut travel distance to nearest supermarket. However, change in distance to supermarket was not associated with BMI change.